Calcium Propionate Supplementation Has Minor Effects on Major Ruminal Bacterial Community Composition of Early Lactation Dairy Cows - Zhang, Fan; Wang, Yue; Wang, Hui; Nan, Xuemei; Guo, Yuming; Xiong, Benhai (Frontiers in Microbiology, 2022)
Calcium propionate is one kind of good source for preventing and treating hypocalcemia and ketosis for dairy cows in early lactation. However, little is known about the effects of different feeding levels of calcium propionate on the ruminal bacterial community of early lactation dairy cows. This study aimed to explore the effects of different calcium propionate feeding levels on the ruminal fermentation and bacterial community composition of early lactation dairy cows. Twenty-four multiparous cows were randomly allocated into control (CON), low calcium propionate (LCaP), medium calcium propionate (MCaP), and high calcium propionate (HCaP) groups with 6 cows per group after calving. The CON group cows were fed the normal total mixed ration (TMR), and the cows of the LCaP, MCaP, and HCaP groups were fed TMR supplemented with 200, 350, and 500 g/d calcium propionate for 35 d after calving, respectively. The rumen fermentation parameters were measured every week, and the ruminal bacterial community composition of the last week was analyzed by 16S rRNA gene sequencing. Under the same diet, the rumen pH showed no difference among the four groups, but the content of microbial crude protein and ammonia nitrogen quadratically decreased and linearly increased with calcium propionate supplementation, respectively. The feeding of calcium propionate linearly increased the concentrations of total volatile fatty acid, acetate, propionate, butyrate, iso-valerate, and valerate in the rumen. In all the treatment groups, Bacteroidetes, Firmicutes, and Proteobacteria were the dominant phyla, and Prevotella_1 and Succiniclasticum were the dominant genera in the rumen. Compared with the CON group, the addition of calcium propionate to the early lactation dairy cows quadratically improved the alpha diversity index of Chao1 estimator and observed species, but had little effect on the relative abundance of the major bacterial at phyla and genera level. These results suggested different levels of calcium propionate supplementation improved the rumen fermentation and the ruminal bacterial diversity but had little impact on the major ruminal bacterial community composition of dairy cows in early lactation.